2000
DOI: 10.4049/jimmunol.165.6.3375
|View full text |Cite
|
Sign up to set email alerts
|

ICAM-1-Coupled Cytoskeletal Rearrangements and Transendothelial Lymphocyte Migration Involve Intracellular Calcium Signaling in Brain Endothelial Cell Lines

Abstract: Endothelium of the cerebral blood vessels, which constitutes the blood-brain barrier, controls adhesion and trafficking of leukocytes into the brain. Investigating signaling pathways triggered by the engagement of adhesion molecules expressed on brain endothelial cells using two rat brain endothelial cell lines (RBE4 and GP8), we report in this paper that ICAM-1 cross-linking induces a sustained tyrosine phosphorylation of the phosphatidylinositol-phospholipase C (PLC)γ1, with a concomitant increase in both in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
220
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(239 citation statements)
references
References 44 publications
15
220
0
2
Order By: Relevance
“…The nonmetastatic ER þ MCF-7 mammospheres showed high expression of ICAM-3 only. ICAM-1 molecules interact with the actincontaining cytoskeleton and a-actinin, inducing cytoskeletal rearrangement (42,43). This activity could explain the neutrophilindependent invasion and dissemination of MDA-MB-231 cancer cells because their high expression of ICAM molecules promotes their increased motility and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…The nonmetastatic ER þ MCF-7 mammospheres showed high expression of ICAM-3 only. ICAM-1 molecules interact with the actincontaining cytoskeleton and a-actinin, inducing cytoskeletal rearrangement (42,43). This activity could explain the neutrophilindependent invasion and dissemination of MDA-MB-231 cancer cells because their high expression of ICAM molecules promotes their increased motility and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that endothelial adhesion molecules are involved in transducing leukocyte adhesion-mediated signaling responses to endothelium, leading to actin cytoskeletal reorganization (Etienne-Manneville et al, 2000;Cook-Mills et al, 2004). Moreover, recent studies have demonstrated that leukocyte adhesion promotes the remodeling of the apical endothelial plasma membrane into projections that surround adherent leukocytes (Carman and Springer, 2004;Shaw et al, 2004;Barreiro et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Within the signaling pathways induced through ligation of ICAM-1, activation of SRC tyrosine kinases has been demonstrated in human umbilical vein ECs and rat brain microvascular ECs (5)(6)(7). In addition, ligation of ICAM-1 induces activation of LYN, a member of the SRC family tyrosine kinases, in a B cell lymphoma line (8).…”
mentioning
confidence: 99%
“…The mechanisms underlying SRC activation in response to ICAM-1 cross-linking have been examined in rat brain microvascular ECs, where activation of SRC requires activation of phospholipase C (6). In these ECs and human umbilical vein ECs, activation of SRC in turn results in tyrosine phosphorylation of cortactin (5-7), an actin-binding protein that modulates the F-actin cytoskeleton as well as EC locomotion (14 -16).…”
mentioning
confidence: 99%